Penerapan Ragam Hias Ni’o afi afi dengan Teknik Circle and Triangles pada Gaun Pengantin - Rut Dhea Epyravita; Yuhri Inang Prihatina (Universitas Negeri Surabaya, 2022)
The purpose of this research is to determine the process of application and the result of the development of ni'o afi-afi ornaments as wedding dress ornaments. Inspired by the folklore of North Sumatra